GLASS – STEEL HYBRID ELEMENTS UNDER FOUR POINT BENDING TEST - Trajanoska, Bojana (Journal of Applied Engineering Science, 2015)
Problems evolving from the brittleness of structural glass result in need of innovative solutions which will improve the post-breakage behaviour of the elements in the structure. As the need of the glass performance gets higher, the fully tempered glass gets in the focus and its usage becomes greater. But although this type of glass gives great performance with its tensile strength and deflection capaciy, it has no residual strength. Due to its breakage pattern into small pieces the collapse of the element may be instant even in laminated glass elements. Thus, increasing the post breakage behaviour is crucial in order to keep the integrity of the tempered glass element. This can be done either by changing the interlayer properties, or including kind of reinforcement in the element structure. This paper presents experimental testing of the performances of steel plate reinforced hybrid glass element under four point bending test. As a result, it shows the improvement in mechanical behaviour of the described hybrid structure concept compared to a monolithic glass element with same dimensions, by means of stress distribution and reinforcement capacity.
Keywords: Stress distribution; Experimental testing; Post breakage; Steel reinforcement; Hybrid elements